Перетворення Лоренца: еволюція підходів до виведення та інтерпретації у період становлення теорії відносності - Щербак, О. А. (НТУ "ХПІ", 2008)
В статье рассмотрены различные подходы к выводу преобразований Лоренца в работах Л. Й. Кордиша и А. П. Грузинцева, Ч. Бялобржескаго, И. Огиеветского, в период становления теории относительности. Проведен их сравнительный анализ, сделаны выводы о характере эволюции представлений о преобразованиях Лоренца.

In the paper studied the different approaches to derivation of Lorentz transformation laws in L. Kordisch', A. Gruzincev', Ch. Byalobrgeskiyu', I. Ogievetckiyu' s papers during becoming the theory of relativity. Their comparative analysis was conducted, the conclusion about character of representations evolution Lorentz transformation laws was made.
Keywords: теорія електродинаміки середовищ; рівняння Лоренца; рівняння Максвела; сталість швидкості світла; дослід Майкельсона-Морлі; теорія відносності